Kajian Corak Pembuat Perjalanan Ke Pusat Membeli Belah Di Seberang Perai Selatan - Abu Bakar, Norafizal Zuraidin (Universiti Sains Malaysia, 2006)
The purpose of this report is to present on the research entitled “Study on Travel Behavior of Shopping Trip makers in Seberang Perai Selatan”. The selected location is the Billion malls in Parit Buntar and The Summit in Bukit Mertajam. Information regarding the path taken to these malls, the visitors and the information of the malls themselves were gathered. The methods applied during the research were using questionnaires with interviews. Through the questionnaire, information regarding the types of transport, the frequency and the duration of visits are analyzed. The effectiveness of the vehicles parking facility is also analyzed. The differences between the two malls are observed to show the advantages and disadvantages that they have. Other than that, the time the male and female visitors spent at the malls is also recorded and generally females spend more time for shopping. Other than that, analysis serves to show the different and similarity of all the researches that have been done before about shopping malls. After that home – mall – home is the highest trip pattern that was taken by the visitors, men and women. It was found that visitors to the mall prefer shopping at a place convenient to them, malls that are nearer to their home and that offer the range of merchandise that they want. These factors are the main attraction for these visitors to come and visit the malls. From this information, it given a rough perspective on the visitors, the path taken and the attractions of the shopping complex.